PENERAPAN APLIKASI SISTEM INFORMASI MANAJEMEN DAN DESIGN LAYANAN DRIVE THRU PADA USAHA KAFE RUMAH SUSU DI PADANG PANJANG - Fitrimawati Fitrimawati; Ramaiyulis Ramaiyulis; Aronal Arief Putra (Jurnal Hilirisasi IPTEKS, 2018)
Science and technology for the community have been applied at the Milk House Cafe located on Kiayi Kamarulloh Street, Bukik Surungan, Padang Panjang city. Along with the development of the business, this dairy café has experienced problems in formulating strategies in business development and increasing sales.One solution is the Management Information System (SIM) approach. The SIM application is conducted so that the partner's business data is complete and accurate and is available at all times. The solution to improving marketing is to make the design of the service drive simple but attractive. Orders are ordered and services are provided through a special window, while consumers remain in their vehicles. The method of implementing this program is the demonstration method. The results of program implementation are SIM applications with complete and accurate partner business data and are available at all times. SIM can provide information to support the decision-making process that the manager will take, allowing decisions to be taken faster and precisely. Processing transactions in SIM allows managers to easily supervise company assets, monitor business developments and provide reports to stakeholders. The solution to improving marketing is to make the design of the service drive simple but attractive. Orders are ordered and services are provided through a special window, while consumers remain in their vehicles. The purpose of the drive thru is to facilitate consumers who want to get products quickly but are reluctant to get off their vehicles (cars / motorbikes). This drive thru service can save consumers time to enjoy fast food. Through this service consumers stop by, can then leave within 3 minutes.